The Financial Conference on Inflation, Washington, D.C., September 20, 1974 : held at the request of President Gerald R. Ford and the Congress of the United States - Simon, William E. ([Washington : Dept. of the Treasury : for sale by the Supt. of Docs., U.S. Govt. Print. Off., 1974)
The book contains the proceedings of the financial conference on inflation. The conference is a bipartisan effort to deal with the domestic problem and the desire on the part of the American public for action to curb inflation.
One of a series of pre-summit sector conferences held prior to the summit Conference on Inflation, Washington, D.C., 1974.
osc 27/3/28
Loans
Keywords: Inflation (Finance); Fiscal policy; Monetary policy